Phosphorous Diffusion in N2+-Implanted Germanium during Flash Lamp Annealing: Influence of Nitrogen on Ge Substrate Damage and Capping Layer Engineering. (1st January 2017) - Skarlatos, D.; Ioannou-Sougleridis, V.; Barozzi, M.; Pepponi, G.; Velessiotis, D.; Skoulikidou, M. C.; Vouroutzis, N. Z.; Papagelis, K.; Dimitrakis, P.; Thomidis, C.; Colombeau, B.
Abstract : In this work we present a systematic study on post-implantation phosphorous diffusion control in Ge by co-implanted nitrogen in combination with various surface capping layers (Al2 O3, SiO2 and Si3 N4 ). Phosphorous has been implanted at low energy (11 keV) and high dose (10 15 cm −2 ) in p-Ge (100) already implanted or not with low energy (10 keV −5 × 10 14 cm −2 ) N2 + . Flash Lamp Annealing (FLA) at 800–850°C for 20 ms in inert ambient has been used as post-implantation annealing scheme. In the absence of nitrogen, significant substrate damage and capping layer deterioration prevents a reliable comparison among the three capping materials. The presence of nitrogen in the Ge substrate, effectively suppresses the damage observed after the FLA. In this case, P diffusion is additionally retarded in the presence of Al2 O3 as compared to SiO2 and Si3 N4 . The experimental results constitute a direct evidence of the action of the three capping layers as sinks for Ge vacancies with different interface recombination velocities. On the contrary, the nitrogen diffusion data suggest that interface recombination velocities of Ge interstitials are almost independent of the capping layer choice.